2017
DOI: 10.7554/elife.28342
|View full text |Cite
|
Sign up to set email alerts
|

COPI mediates recycling of an exocytic SNARE by recognition of a ubiquitin sorting signal

Abstract: The COPI coat forms transport vesicles from the Golgi complex and plays a poorly defined role in endocytic trafficking. Here we show that COPI binds K63-linked polyubiquitin and this interaction is crucial for trafficking of a ubiquitinated yeast SNARE (Snc1). Snc1 is a v-SNARE that drives fusion of exocytic vesicles with the plasma membrane, and then recycles through the endocytic pathway to the Golgi for reuse in exocytosis. Removal of ubiquitin from Snc1, or deletion of a β'-COP subunit propeller domain tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 63 publications
(115 reference statements)
5
92
0
Order By: Relevance
“…The localization to COPI‐positive structures raises the interesting possibility that Atg9 cycles between the endosomal system and the Golgi thereby connecting different compartments recently implicated in autophagosome formation . It has also recently been published that a fraction of COPI binds polyubiquitinated cargo in endosomes for delivery to late‐Golgi . However, for technical reasons, we could not assay co‐localization of GFP‐Atg9 with the Sec7‐mCherry, Snf7‐mCherry or Vam6‐mCherry markers.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The localization to COPI‐positive structures raises the interesting possibility that Atg9 cycles between the endosomal system and the Golgi thereby connecting different compartments recently implicated in autophagosome formation . It has also recently been published that a fraction of COPI binds polyubiquitinated cargo in endosomes for delivery to late‐Golgi . However, for technical reasons, we could not assay co‐localization of GFP‐Atg9 with the Sec7‐mCherry, Snf7‐mCherry or Vam6‐mCherry markers.…”
Section: Resultsmentioning
confidence: 88%
“…All scale bars are 5 μm for delivery to late-Golgi. 35 However, for technical reasons, we could not assay co-localization of GFP-Atg9 with the Sec7-mCherry, Snf7-mCherry or Vam6-mCherry markers.…”
Section: Co-localization Identifies New Endomembrane System Proteinsmentioning
confidence: 99%
“…First, the cellular mechanisms by which mutant Copa in thymic epithelial cells leads to a defect in negative selection remains unclear. Disruptions in COPI trafficking have been shown to alter endolysosomal function and macroautophagy (1,(37)(38)(39), cellular processes important in the proteolysis and loading of self-proteins onto MHC molecules (40, 41). We previously showed that cell lines derived from COPA syndrome patients demonstrate a constellation of morphological and 14 functional findings that suggest impaired macroautophagy (1).…”
Section: Discussionmentioning
confidence: 99%
“…These motifs contact the propeller domain of α-or β'-COP that are ideally positioned adjacent to the surface of the membrane (Eugster et al, 2004;Jackson et al, 2012;Ma and Goldberg, 2013;Schroder-Kohne et al, 1998). A second site in the propeller domain of β'-COP also regulates recycling of the exocytic SNARE Snc1 by recognizing polyubiquitylated Snc1 (Xu et al, 2017). Arginine (R)-based ER retrieval signals (ɸRxR; in which ɸ represents any hydrophobic amino acid) are another class of sorting signals on the cytoplasmic domains of heteromultimeric proteins, such as channels and receptors (Zerangue et al, 1999(Zerangue et al, , 2001.…”
Section: Cargo Recognition By Copimentioning
confidence: 99%